2019
DOI: 10.4018/ijt.2019070101
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Precise Manufacturing and Responsible Innovation

Abstract: Althoughcontinuedinvestmentsinnanotechnologyaremade,atomicallyprecisemanufacturing(APM) todateisstillregardedasspeculativetechnology.APM,alsoknownasmolecularmanufacturing,is atokenexampleofaconvergingtechnology,hasgreatpotentialtoimpactandbeaffectedbyother emergingtechnologies,suchasartificialintelligence,biotechnology,andICT.Thedevelopmentof APMthuscanhavedrasticglobalimpactsdependingonhowitisdesignedandused.Thisarticleargues thattheethicalissuesthatarisefromAPM-asbothastandalonetechnologyorasaconvergingoneaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Particular emphasis is given to the involvement and elicitation of stakeholders, either those directly or indirectly implicated by technology design. Approaches such as universal design [39], inclusive design [40], sustainable design [41], participatory design [42], and values sensitive design [43][44][45], among others have been theorized; Value Sensitive Design (VSD) becoming one of the most popular approaches over the last 20 years [46]. Emerging from the field of human-computer interaction, VSD is precisely predicated on the same premise that technology is not value-neutral, rather it is sensitive to stakeholder values, whether they are direct stakeholders such as users and designers or indirect such as industry CEO's, governments, and the biosphere at large [35,47].…”
Section: Value Sensitive Design In the Industry 50 Eramentioning
confidence: 99%
See 2 more Smart Citations
“…Particular emphasis is given to the involvement and elicitation of stakeholders, either those directly or indirectly implicated by technology design. Approaches such as universal design [39], inclusive design [40], sustainable design [41], participatory design [42], and values sensitive design [43][44][45], among others have been theorized; Value Sensitive Design (VSD) becoming one of the most popular approaches over the last 20 years [46]. Emerging from the field of human-computer interaction, VSD is precisely predicated on the same premise that technology is not value-neutral, rather it is sensitive to stakeholder values, whether they are direct stakeholders such as users and designers or indirect such as industry CEO's, governments, and the biosphere at large [35,47].…”
Section: Value Sensitive Design In the Industry 50 Eramentioning
confidence: 99%
“…However, it works speculatively too for future technologies, both near and long term. Examples include its exploratory application to nanopharmaceuticals [55], molecular manufacturing [45], intelligent agent systems [56], and, less futuristic, autonomous vehicles [57]. Although these studies provide useful illustrations of the intricacies of how the VSD approach can be accommodated to various technologies in particular, they do not provide discussions of the convergence factor of these technologies in general or how they can be designed with this structural embeddedness and interdependence.…”
Section: Value Sensitive Design In the Industry 50 Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, the VSD methodology is typically employed in technological design where human values come into conflict with each other and where the design solutions are of considerable ethical concern [27]. Similar to how Friedman, Kahn, and Borning [7] used VSD in the realm of human-computer interaction to show how the values of privacy and usability needed to be balanced, Umbrello [14] demonstrated that stakeholders involved in the development of AI in the United Kingdom prized addition values. These comprised transparency, control, data privacy, and security, all of which need to be delicately balanced through careful stakeholder coordination and cooperation.…”
Section: Emerging Issues With Autonomous Vehiclesmentioning
confidence: 99%
“…To the best of our knowledge, this is the first paper to evaluate the suitability of the VSD approach to AI as it pertains to the values of explainability and verifiability for AVs [5]. Prior literature on VSD has focused on its methodological foundations [6][7][8], its applicability to existing technologies, such as energy systems and care robotics [9][10][11], as well as its applicability to AI in general and other advanced technologies for instance, molecular manufacturing [12][13][14][15]. These studies provide useful information on the VSD approach in general, as well as why, and how it can be used for the development of IAs like AVs.…”
Section: Introductionmentioning
confidence: 99%